Curriculum Development Foundations in the Implementation Components of Islamic Religious Education Learning - Asna, Ni'am Khurotul; Nevinavila; Hasanah, Abidatul (Journal of Educational Research and Practice, 2023)
This article is prepared to elaborate on the foundations of developing the Islamic Education curriculum. The research method employed in this study is the method of library research. Library research involves gathering data or materials originating from libraries, such as books, dictionaries, journals, encyclopedias, documents, magazines, and similar sources. Consequently, the data obtained from the literature review is described as it is.The article discusses that a curriculum, in general, constitutes a plan or arrangement concerning the subject matter and serves as a guide for conducting learning activities. In the realm of Islamic Education curriculum, it is a learning design comprising a learning planning program, a learning program, and Islamic educational learning experiences for students to grow into individuals who have faith and piety towards Allah SWT and possess life skills based on Islamic teachings.Several foundations for developing the Islamic Education curriculum include theological, philosophical, psychological, sociological, scientific, and technological bases. These curriculum development foundations should generally serve as the basis, ideas, or principles in conducting learning to achieve the intended learning goals. Specifically, the curriculum development foundations also act as principles in developing, reconstructing, and actualizing the Islamic Education curriculum directed towards contextualizing the students' academic development.